2020
DOI: 10.1186/s12916-020-01693-9
|View full text |Cite
|
Sign up to set email alerts
|

“The post-COVID era”: challenges in the treatment of substance use disorder (SUD) after the pandemic

Abstract: Background Citizens affected by substance use disorders are high-risk populations for both SARS-CoV-2 infection and COVID-19-related mortality. Relevant vulnerabilities to COVID-19 in people who suffer substance use disorders are described in previous communications. The COVID-19 pandemic offers a unique opportunity to reshape and update addiction treatment networks. Main body Renewed treatment systems should be based on these seven pillars: (1) telemedicine and digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 50 publications
0
51
0
2
Order By: Relevance
“…Much of the evidence makes recommendations around telehealth [ 14 , 25 , 32 , 33 ] as well as describing other technology that HR services could utilize, including smartphone and web-based interventions, text messaging for continuing contact and care, machine learning and wearable devices, including digital phenotyping and ecological momentary assessment, biofeedback and virtual reality [ 34 , 35 ]. Lead time and availability of technology (for both services and clients) will limit implementation of these options in the short term with text-messaging, smartphone and web-based interventions being the most simple and quick to roll-out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the evidence makes recommendations around telehealth [ 14 , 25 , 32 , 33 ] as well as describing other technology that HR services could utilize, including smartphone and web-based interventions, text messaging for continuing contact and care, machine learning and wearable devices, including digital phenotyping and ecological momentary assessment, biofeedback and virtual reality [ 34 , 35 ]. Lead time and availability of technology (for both services and clients) will limit implementation of these options in the short term with text-messaging, smartphone and web-based interventions being the most simple and quick to roll-out.…”
Section: Resultsmentioning
confidence: 99%
“…Links to social and economic services were also emphasized as important. For instance, ‘Housing First’ was highlighted as an approach which can facilitate social distancing and provide stability for PWID to engage in HR and manage extended OST take home doses appropriately [ 33 , 34 ]. With increased duration of take home OST, one review concluded that accommodation for the homeless should have capacity for the safe storage of medications and space to designate as a safer use room [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second, the topics and references. Category Topic and references Change to medical practice Mental health care [254] , [257] , [261] , [273] , [274] , [275] ; Emergency care [276] , [277] ; Substance abuse [253] , [263] , [278] , [279] , [280] ; Oncological care [264] , [281] Health care practices [255] , [259] , [262] , [282] , [283] , [284] ; Pediatric care [283] , [285] Other care [256] , [260] , [268] , [286] , [287] , [288] Modeling Modeling approaches [28] , [265] , [289] , [290] , [291] , [292] , [293] ; Transmission dynamics [294] , [295] , [296] , [297] , [298] Mobile phone data [29] ; estimation [258] Effect of NPIs Effects on: children ...…”
Section: Comments And/or Perspectivesmentioning
confidence: 99%
“…This is the largest group of comments and/or perspectives. We find articles focused on a range of medical specialities: mental health care [254] , [257] , [261] , [273] , [274] , [275] , emergency care [276] , [277] , substance abuse [253] , [263] , [278] , [279] , [280] , oncological care [264] , [281] , health care practices [255] , [259] , [262] , [282] , [283] , [284] , pediatric care [283] , [285] , and other care [256] , [260] , [268] , [286] , [287] , [288] .…”
Section: Comments And/or Perspectivesmentioning
confidence: 99%
“…Ashamed individuals might blame themselves rather than others, believing that failures reflect inadequacy in themselves. Shame often originates from incorrect perception or belief in particular events, and it may be an underlying mechanism in which stigma is enacted [ 27 ]. Concerning infectious disease-perceived discrimination, individuals may exhibit feelings of shame and stigmatization synchronously.…”
Section: Introductionmentioning
confidence: 99%